Relation between Dental Caries and mood in 12-year-old schoolchildren from Huayna-Cápac Parish, Cuenca-Ecuador, 2016 - Ordoñez-Quezada, Carolina M. (2020)
Dental caries is one of the most prevalent pathologies worldwide, it affects people's well-being and their quality of life. The recommended indicator to know the history of present and past dental caries is through the number of decayed, lost and filled teeth in the permanent dentition known as index CPO-D Objective: The purpose of this study was to relate DMFT index and mood in 12-year-old schoolchildren from Huayna-Capac parish, Cuenca, 2016. Materials and methods: It is a descriptive, retrospective study, analyzed 152 dental records  belonging to educational institutions in this urban area. The statistical test that was used was Kendall's Tau-b Coefficient of Concordance with a 95% certainty. Results: The predominant level of CPO-D was the mean risk in 25,7%, standing out in the female sex, only 21,1% of the participants perceived some impact on mood and a level of significance greater than that was found 5% (p = 0,851) between CPO-D level and mood. Conclusion: Despite the absence of correlation between the variables, the risk of dental caries is moderate, so it is necessary to continue providing preventive education in oral health, to improve oral habits and therefore the incidence of caries.